Оптимізація режимів спільної роботи нагрівальної печі й прокатного стану з використанням енергозберігаючих екранів - Перерва, В. Я.; Шевченко, Г. Л.; Губинський, М. В. (НТУ "ХПІ", 2009)
The optimization task of the joint work of the heating furnace and table rolling with the energy-saving screens installation was solved. An optimal temperature range of the metal heat in the furnace ensuring reduction in the finished steel value at 0,2–0,5%, was received.
Keywords: енергозбереження; ресурсозбереження; прокатний стан; нагрівальна піч; температура нагріву; енергозберігаючий екран